Computing imaging in shortwave infrared bands enabled by MoTe2/Si 2D‐3D heterojunction‐based photodiode - Dongfeng Shi; Jiawang Chen; Menglei Zhu; Zijun Guo; Zixin He; Ming Li; Di Wu; Yingjian Wang; Liang Li (InfoMat)
Abstract Breakthroughs brought about by two‐dimensional (2D) materials in the field of photodetection have opened up new possibilities in infrared imaging. However, challenges still exist in fabricating high‐density detector arrays using such materials, which are essential for traditional imaging systems. In this study, we present a state‐of‐the‐art computing imaging system that utilizes a MoTe2/Si self‐powered photodetector coupled with flexible Hadamard modulation algorithms. This system demonstrates remarkable capability to produce high‐quality images in the shortwave infrared (SWIR) band, surpassing the capabilities of devices based on alternative material systems. The exceptional infrared imaging capability primarily stems from the MoTe2/Si photodetector's inherent features, including an ultra‐wide spectral range (265–1550 nm) and extremely high sensitivity (linear dynamic range (LDR) up to 123 dB, responsivity (R) up to 0.33 A W–1, external quantum efficiency (EQE) up to 43% and a specific detectivity (D*) exceeding 2.9 × 1011 Jones). Moreover, the imaging system demonstrates the ability to achieve high‐quality edge imaging of objects in the SWIR band (1550 nm), even in strong scattering environments and under low sampling rate conditions (sampling rate of 25%). We believe that this work will effectively advance the application scope of 2D materials in the field of computational imaging in SWIR bands.